Faculty Perception on Support to Do Their Job Well - Charissa K. Eaton; Aurea K. Osgood; Dawnette L. Cigrand; Ann-Marie L. Dunbar (Park University, 2015)
Research has commonly suggested that adequate and appropriate mentoring and faculty perception of support for a work-life balance are important factors in the recruitment, development, and retention of university faculty. To better understand the role of these factors in faculty job performance at teaching universities, faculty from such a university were surveyed about their experiences with these forms of support and the factors that influenced their perception of the ability to do their job well. Results indicate that faculty mentoring was an important predictor for support at the department level. Additionally, perceived work-life balance was a significant factor at the college and university levels.